2008
DOI: 10.1103/physrevlett.100.155002
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Demonstration of Plasma-Drag Acceleration of a Dust Cloud to Hypervelocities

Abstract: Simultaneous acceleration of hundreds of dust particles to hypervelocities by collimated plasma flows ejected from a coaxial gun is demonstrated. Graphite and diamond grains with radii between 5 and 30 microm, and flying at speeds up to 3.7 km/s, have been recorded with a high-speed camera. The observations agree well with a model for plasma-drag acceleration of microparticles much larger than the plasma screening length.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Experiments have confirmed that the ion drag force can propel the dust particles and accelerates them to speeds up to a few km/s. 10,24,26 The ion drag force is proportional with the plasma density and its flow speed. Our proposed dust removal technique is based on the drag force exerted by the plasma flow at a reduced pressure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments have confirmed that the ion drag force can propel the dust particles and accelerates them to speeds up to a few km/s. 10,24,26 The ion drag force is proportional with the plasma density and its flow speed. Our proposed dust removal technique is based on the drag force exerted by the plasma flow at a reduced pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Initially a) catalin.ticos@inflpr.ro proposed for confining and focusing the plasma in order to obtain fusion-like conditions, 8 the coaxial gun has found some utility in topics connected to fusion research such as fueling of tokamaks, 9 dust acceleration to hypervelocity, 10 and merging of plasma jets. 11 Other applications are in material science studies for ion implantation on surfaces 12 or in fundamental plasma dynamics studies.…”
Section: Introductionmentioning
confidence: 99%
“…Starkbroadening measurement did show that dense plasmas of 10 22 m −3 density has been created. 37 Downstream in the FMP chamber provided more room for diagnostics. In Fig.…”
Section: B Results From the Type II Experimentsmentioning
confidence: 99%
“…Details about many applications of dust injection can be found in the literature [3][4][5]. We summarize the required velocities and dust sizes for some of the fusion-energy results in Fig.…”
Section: Three Regimes Of Dust Injection For Fusion Energymentioning
confidence: 99%